Burden or Opportunity? Parent Experiences When Approached for Research in a Pediatric Intensive Care Unit. Issue 3 (20th May 2019) - Paquette, Erin; Shukla, Avani; Davidson, Jacob; Rychlik, Karen; Davis, Matthew
ABSTRACT: Despite an ongoing need for pediatric research, low study enrollment may impede study completion, particularly in critical care. We conducted a prospective cross‐sectional survey and chart review study to assess parent experiences with research in a pediatric intensive care unit (PICU). Of the 80 parents who completed the study survey, 54% were approached to participate in a research study in the PICU, and 93% agreed to participate. Motivators included altruism, low burden, low risk, and research that would benefit the child. Barriers included risks to the child, the child's being too sick to participate, feeling overwhelmed, not having enough time to participate, the research's being burdensome, and the research's not being explained well. PICU parents had mostly favorable attitudes toward research participation. Compared with non‐Hispanic survey respondents, respondents of Hispanic ethnicity less often reported having been approached for research, which further evidences the need to track research recruitment processes to help avoid underinclusion of members of minority populations.